STUDENT MATHEMATIC DAYA AFTER LEARNING CONTEXTUAL BASED COOPERATIVE - Rusli Umar (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2013)
This research is an experimental research that investigates the mathematical power (mathematical power) of junior high school students in the subject matter of comparison. Mathematical power in question is the ability of reasoning and communication, connection capabilities, and problem-solving skills. In addition to mathematical power, also investigated the activities of students and teachers as well as student responses to learning. The experimental unit in this research is the students of Class VII of SMPN 1 Bulukumba in even semester of the 2008/2009 school year. Selection of experimental unit used is cluster random sampling. All the selected students (Grade VII2) as many as 30 people were used as experimental units in this study. Data analysis used is descriptive analysis. The results showed that: (1) the average score of reasoning and communication ability, connection ability, and problem-solving ability of Grade VII students of SMP Negeri 1 Bulukumba after being taught through cooperative contextual learning were in high category (2) All aspects observed are within the ideal timeframe (3) teacher activity in the learning process is generally implemented entirely (4) in general the students give positive responses to cooperative based learning contextual, as the implication of the results of this study, it is suggested that in learning mathematics, Teachers should use cooperative learning contextually